2022
DOI: 10.1111/biom.13657
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Inflated Poisson Models with Measurement Error in the Response

Abstract: Zero-inflated count data arise frequently from genomics studies. Analysis of such data is often based on a mixture model which facilitates excess zeros in combination with a Poisson distribution, and various inference methods have been proposed under such a model. Those analysis procedures, however, are challenged by the presence of measurement error in count responses. In this article, we propose a new measurement error model to describe error-contaminated count data. We show that ignoring the measurement err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Instead, we generated the data through computer simulation using R, following these steps: The beta values and conditions were used in Lalonde's (2014) study, which have been shown to greatly affect the relative bias, error rate, and power of the models. Some studies also consider the potential impact of measurement errors in the response variable, a complication Zhang and Yi (2023) addressed in their work on ZIP models. Their methodology provides a foundation for dealing with measurement errors.…”
Section: Data Generationmentioning
confidence: 99%
“…Instead, we generated the data through computer simulation using R, following these steps: The beta values and conditions were used in Lalonde's (2014) study, which have been shown to greatly affect the relative bias, error rate, and power of the models. Some studies also consider the potential impact of measurement errors in the response variable, a complication Zhang and Yi (2023) addressed in their work on ZIP models. Their methodology provides a foundation for dealing with measurement errors.…”
Section: Data Generationmentioning
confidence: 99%
“…This model-based approach is simple and flexible, and it lends itself to easier interpretation compared to transformation-based approaches. To address sparsity and over-dispersion, common strategies in microbiome data analysis involve the use of zero-inflated Poisson or negative-binomial models [28,29]. However, it is worth noting that most existing methods for differential abundance analysis, or more generally, association analysis, fail to account for compositionality [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review on the past and current trends for the models and monitoring of ZI processes is available in Mahmood and Xie (2019). Zhang and Yi (2022) have discussed about the Zero-inflated Poisson models with measurement error in the response. Tian et al (2022) introduced the zero-inflated non-central negative binomial (ZINNB) distribution and presented the maximum likelihood estimation method for estimation of the parameters of the ZINNB distribution.…”
Section: Introductionmentioning
confidence: 99%